The Role of Endogenous Neuroprotective Mechanisms in the Prevention of Retinal Ganglion Cells Degeneration - Pietrucha-Dutczak, Marita; Amadio, Marialaura; Govoni, Stefano; Lewin-Kowalik, Joanna; Smedowski, Adrian (Frontiers in Neuroscience, 2018)
Retinal neurons are not able to undergo spontaneous regeneration in response to damage. A variety of stressors, i.e., UV radiation, high temperature, ischemia, allergens, and others, induce reactive oxygen species production, resulting in consecutive alteration of stress-response gene expression and finally can lead to cell apoptosis. Neurons have developed their own endogenous cellular protective systems. Some of them are preventing cell death and others are allowing functional recovery after injury. The high efficiency of these mechanisms is crucial for cell survival. In this review we focus on the contribution of the most recently studied endogenous neuroprotective factors involved in retinal ganglion cell (RGC) survival, among which, neurotrophic factors and their signaling pathways, processes regulating the redox status, and different pathways regulating cell death are the most important. Additionally, we summarize currently ongoing clinical trials for therapies for RGC degeneration and optic neuropathies, including glaucoma. Knowledge of the endogenous cellular protective mechanisms may help in the development of effective therapies and potential novel therapeutic targets in order to achieve progress in the treatment of retinal and optic nerve diseases.